Knowledge Representation and Management, It’s Time to Integrate! - Dhombres, F.; Charlet, J.; Section Editors for the IMIA Yearbook Section on Knowledge Representation and Management (Yearbook of Medical Informatics, 2017)
Objectives: To select, present, and summarize the best papers published in 2016 in the field of Knowledge Representation and Management (KRM).Methods: A comprehensive and standardized review of the medical informatics literature was performed based on a PubMed query.Results: Among the 1,421 retrieved papers, the review process resulted in the selection of four best papers focused on the integration of heterogeneous data via the development and the alignment of terminological resources. In the first article, the authors provide a curated and standardized version of the publicly available US FDA Adverse Event Reporting System. Such a resource will improve the quality of the underlying data, and enable standardized analyses using common vocabularies. The second article describes a project developed in order to facilitate heterogeneous data integration in the i2b2 framework. The originality is to allow users integrate the data described in different terminologies and to build a new repository, with a unique model able to support the representation of the various data. The third paper is dedicated to model the association between multiple phenotypic traits described within the Human Phenotype Ontology (HPO) and the corresponding genotype in the specific context of rare diseases (rare variants). Finally, the fourth paper presents solutions to annotation-ontology mapping in genome-scale data. Of particular interest in this work is the Experimental Factor Ontology (EFO) and its generic association model, the Ontology of Biomedical AssociatioN (OBAN).Conclusion: Ontologies have started to show their efficiency to integrate medical data for various tasks in medical informatics: electronic health records data management, clinical research, and knowledge-based systems development.
Keywords: Knowledge representation (computer); biomedical ontologies; controlled vocabularies; information storage and retrieval; data integration